LEGAL PROTECTION FOR CONSUMERS AGAINST MEDICINAL PRODUCTS THAT POSE HEALTH RISKS: OPTIMIZING THE SUPERVISORY ROLE OF THE INDONESIAN FOOD AND DRUG AUTHORITY (BPOM) FROM THE PERSPECTIVE OF THE RULE OF LAW - Aulia Jasmine Ayu Malika; Himawan Sugiharto; Soesi Idayanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
As a rule of law state that embraces the welfare state concept, Indonesia has an affirmative obligation to safeguard the safety of its citizens through the supervision of high-risk pharmaceutical products. The 2022 outbreak of Atypical Progressive Acute Kidney Injury (APAKI), caused by contamination with Ethylene Glycol (EG) and Diethylene Glycol (DEG) in syrup-based medicinal products, which resulted in the deaths of 324 children, underscores the urgent need to reconstruct the pharmaceutical regulatory oversight system. This study employs a normative juridical research method using statutory, case, and conceptual approaches. The findings indicate that the pre-market and post-market supervisory functions carried out by the Indonesian Food and Drug Authority (BPOM) have not been implemented optimally due to structural constraints, limited resources, and insufficient responsiveness to the evolving risks associated with modern pharmaceutical preparations. Grounded in the Responsive Law Theory and the concept of law as a tool of social engineering, the optimization of preventive and repressive legal protection for consumers must be achieved through the transformation of risk-based supervision, strengthening the accountability of state liability, digitalization of the pharmaceutical supply chain, and the integration of inter-institutional regulatory oversight. Keywords: Consumer Protection, Indonesian Food and Drug Authority (BPOM), Optimization of Regulatory Oversight, Rule of Law, High-Risk Medicinal Products.